Social Network Analysis of the Government's Mobility Restriction Policy in Indonesia During Covid-19 Pandemic - Bangkit A. Wiryawan; Satria Aji Imawan (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
In order to mitigate the adverse effect of Covid-19 pandemic, the government of Indonesia enforced mobility restriction policy (PSBB) between April and July 2020. This policy was met with various responses from the fastly growing digital space. We capture 8000 Indonesian twitter conversation on the issue. Social Network Analysis is applied to identify different role of users in amplifying the policy either positively or negatively. We identify three main actors with government related actors and the media positioned closely. However, contrasting opinion by the opposition dominates the conversation and they affect public perception on the government’s PSBB policy. The findings recall the current debate of the need for content moderation by social media user community to mitigate public opinion manipulation by influencers.